(3GdEaUGM Yf hLhO TQcGJ GdeMGU (B: s (3OQGSI ebGQfI eY GdbGfhf GdbWQi (B/ s - (3KGfj Hf Ydj Hf SYhO Hf YHOGdYRjR Bd KGfj s; (3SejMI eUWai GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2017)
(3JabO GdeMGUI UaI GdGSJKeGQ, hJUHM eMGUI XGgQI ,EPG JONd CMO GdTQcGA aj CYeGd GdEOGQI GdNGQLjI ddTQcI , eJj cGf gPG GdJONd jMed GdeJYGbO GdCNQ Ydj GdEYJbGO HCf gPG GdTQjc jdJRe TNUjG aj ehGLgJg,Ch Cf GdJYgO jJe deUdMJg(B. (3JTJQc GdeMGUI hGdTQcI GdaYdjI aj Cf cdkG efgeG de jJe TgQgG(B. (3GdeMGUI TQcI CTNGU jYQa HYVge GdHYV dJhaQ GdKbI Hjfge s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb, (B2017(3, bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B177-181s
Keywords: (3TQcI GdeMGUIs; (3NUGFU TQcI GdeMGUI aj GdJTQjYjf GdeUQj hGdbWQjs; (3EOGQI TQcI GdeMGUIs; (3hSGFd cTa GdESJJGQ Yf TQcI GdeMGUIs; (3GfbVGA TQcI GdeMGUIs; (3bhGYO GdJUajI aj TQcI GdeMGUIs; (3hSGFd GdcTa Yf hLhO YbO TQcI GdeMGUIs; (3GdfXGe GdbGfhfj dTQcI GdeMGUI aj GdbGfhf GdbWQjs; (3GdfXGe GdbGfhfj dTQcI GdeMGUI aj GdbGfhf GdeUQjs; (3BKGQ EOGQI TQcI GdeMGUIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs